Investigation of correlation between dielectric parameters and nanostructures in aqueous solution grown poly(vinyl alcohol)-montmorillonite clay nanocomposites by dielectric relaxation spectroscopy (eXPRESS Polymer Letters)
Poly(vinyl alcohol) (PVA)-montmorillonite (MMT) clay nanocomposite films up to 10 wt% clay concentration were synthesized by aqueous solution grown technique. The relative complex dielectric function, alternating current electrical conductivity, electric modulus and impedance properties of these organic-inorganic nanocomposites were investigated in the frequency range from 20 Hz to 1 MHz at ambient temperature. The PVA-MMT clay nanocomposite films show a large decrease in the real part and loss of relative dielectric function at 1 wt% MMT clay loading compared to pure PVA film and anomalous behaviour is observed with further increase of clay concentration in PVA matrix. Two dielectric relaxation processes were observed in these nanocomposites; a high frequency relaxation associated with PVA segmental motion and a low frequency relaxation resulting from PVA/dispersed MMT clay interfacial polarization (Maxwell-Wagner relaxation). Dielectric relaxation times corresponding to these processes were determined by fitting dc conductivity corrected complex dielectric function data to the Havriliak-Negami expression. A correlation between change in dielectric relaxation strength, relaxation time and hindrance to the PVA-chain dynamics with the degree of exfoliated structures of dispersed nanoscale MMT clay filler in the PVA matrix were explored. Results confirm the application of dielectric relaxation spectroscopy as a potential tool in the confirmation of nanocomposite formation and their structure characterization.